Beyond Hydrolysis: Scalable, On-Demand Dihydrogen Release from NaBH4 Enables Circular and Sustainable Process Design - Wessels, Pier W.; Verhoef, Caroline J.; Buß, Florenz; Geiger, Valentin; de Jong, G. Bas; Wesselingh, Tim; Germanacos, Philip; Slootweg, J. Chris (Sustainability & Circularity NOW, 2025)
Hydrogen storage in its elemental form poses significant safety and economic challenges. Metal hydrides, particularly sodium borohydride, offer a promising alternative because of their superior safety profiles and enhanced transportability. This study presents a scalable hydrogen release system based on sodium borohydride and commercially available alcohols and acids. The system enables rapid, controlled hydrogen generation, achieving quantitative yields. Quantum chemical calculations were performed to propose a mechanism for the alcoholysis of NaBH4 with isopropyl alcohol (IPA) and acid present. It was demonstrated that the reaction proceeds via isopropoxy-substituted borane derivatives BH(3−n)(OiPr)n (for n = 0, 1, 2, 3), which can form Lewis acid–base adducts with IPA. These Lewis acid–base adducts serve as reaction complexes for σ-bond metathesis, upon which an equivalent of hydrogen gas is released. Notably, the spent fuel can be regenerated to sodium borohydride using established chemical reactions, ensuring the system's sustainability and applicability for larger-scale hydrogen production.
Keywords: Hydrogen storage; NaBH4; Energy transition; Alcoholysis; Semi-alcoholysis